Necrosis Description of Mice Liver Induced with Monosodium Glutamate and Methanol Robusta Coffee Bean Extract (Coffea canephora) - Al-Zuhroh, Tisya Yumn; Santoso, Kuncoro Puguh; Yunita, Maya Nurwartanti; Hidajati, Nove; Praja, Ratih Novita (Universitas Airlangga, 2021)
This study aimed to analyze the effect of methanol robusta coffee bean extract (Coffea canephora) on liver histopathological description in mice induced with monosodium glutamate (MSG). This study was used 20 male mice for 5 treatment groups: K + (MSG 0.12 mg and Vitamin C 6 mg), K- (MSG 0.12 mg and CMC Na 0.1 ml), P1 (MSG 0.12 mg and RCE 0.1 mg), P2 (MSG 0.12 mg and RCE 0.2 mg), and P3 (MSG 0.12 mg and RCE 0.4 mg) per orally for 42 days. Liver histological scores were analyzed using Kruskal Wallis test. The results of Kruskal Wallis test scored p=0,391 which indicates that the data is not significant (p>0.05). In the control and treatment groups there were no significant. In conclusion, the giving methanol robusta coffee bean extract did not show a decrease in hepatosite damage that was different from the negative control treatment group.